Opportunistic mammography screening by the Brazilian Unified Health System in 2019 - Freitas-Junior, Ruffo; Netto Rodrigues, Danielle Cristina; Corrêa, Rosangela Silveira; Oliveira, Luis Fernando Pádua; Couto, Lilian Soares; Urban, Linei Augusta Brolini Dellê; Rahal, Rosemar Macedo Sousa (Mastology, 2020)
Introduction: Mammography screening has been the best method for detecting early tumors and reducing breast cancer mortality according to different studies. In Brazil, the number of women who undergo mammography tests by the Brazilian Unified Health System (SUS) has been far below international recommendations. Objective: To describe the number of mammographies, mammography coverage, and the amount spent on this exam during 2019 by SUS, in Brazil. Method: Ecological study with data from the Department of Informatics of the Brazilian Unified Health System and the Brazilian Institute for Geography and Statistics in order to verify the number of mammographies performed by the SUS concerning the Brazilian female population in Brazil, in the age group of 50 to 69 years, in the states and in macro-regions during 2019. Results: In 2019, 2,660,469 mammographies were performed in the country out of the expected total of 12,154,979, accounting for a 21.9% mammography coverage by SUS at the cost of BRL 117,841,231.97. The lowest coverage rates were verified in the states of Amapá (0.6%) and the Federal District (4.9%), whereas the best rates were found in the states of Paraná (29.7%) and Alagoas (29.6%). Conclusions: The number of mammographies performed in Brazil in 2019 by SUS corresponded to almost ¼ of the country’s need, with mammography coverage far below the target and being widely different among the many Brazilian states.